Cinema's Vital Histories: Wabi-Cinema, Forces and the Aesthetics of Resistance. Issue 3 (October 2017) - Martin, Philip
Abstract : Many films, both narrative and documentary, explore the relationship between history and politics or ethics. This may be accomplished when fictional narrative films enact ethical arguments regarding history in cinematic form, when documentary films explicitly seek to uncover lost histories of political oppression, or films may experientially and aesthetically stage ethical experience with respect to historical meanings and contexts. There are some cases where such ethical-historical experience is explored through the specific aesthetic form of the film in relation to its narrative . Ask This of Rikyū ( Rikyū ni tazuneyo, Tanaka Mitsutoshi, 2013) is one such example. In this paper, I will suggest that film can explore the relation of aesthetic experience to the ethico-political character of history, opening up ways of responding aesthetically to concrete political conditions. Ask This of Rikyū accomplishes this by interrogating the possibility of a wabi-cinema, established with respect to its title character, his individual aesthetic practices, and his personal political circumstances. I will draw upon the work of Gilles Deleuze alongside Kyōto School philosopher Nishida Kitarō in order to articulate the way in which Ask This of Rikyū explores the relation of artistic activity and aesthetic experience to the general ethical and political forces that feed into history.